BOOSTING LEARNING IN PHYSICS AND CHEMISTRY: CHATGPT VIRTUAL ASSISTANTS AND BLOOM'S TAXONOMY FOR UNDERGRADUATES - DIAZ-RUIZ, JULIÁN (2024)
THIS STUDY WAS DEVELOPED WITH THE OBJECTIVE OF DETERMINING THE LEARNING IMPULSE IN PHYSICS AND CHEMISTRY BY USING CHATGPT VIRTUAL ASSISTANTS AND BLOOM'S TAXONOMY IN UNIVERSITY STUDENTS, THE METHODOLOGY WAS QUANTITATIVE AND A LIKERT SCALE QUESTIONNAIRE WAS APPLIED FOR DATA COLLECTION, WHICH WAS CARRIED OUT IN A PRIVATE UNIVERSITY IN PERU. THE SAMPLE CONSISTED OF 120 PHYSICS AND 130 CHEMISTRY STUDENTS. AS PART OF THE RESULTS, IT WAS FOUND THAT 94% OF THE PARTICIPANTS HAVE A POSITIVE OPINION TOWARDS THE USE OF THE CHAT GPT VIRTUAL ASSISTANTS, IN THE SAME ORDER IT WAS FOUND THAT 88.4% CONFIRMED THAT THEY WERE IN THE HIGH LEVEL, IN RELATION TO AN IMPROVEMENT ASSOCIATED WITH SCIENTIFIC COMMUNICATION, 87.6% WERE IN THE SAME POSITION IN THE CATEGORY ANALYZE DATA AND EVIDENCE AND WITH RESPECT TO CALCULATE, OBTAIN AND EVALUATE RESULTS, THIS REACHED 88.8% ON THE HIGHEST RUNG. FROM THE ABOVE, IT WAS CONCLUDED THAT THE PRESENCE OF VIRTUAL ASSISTANTS USED BY THE TEACHER AS A RESOURCE BOOSTED LEARNING IN PHYSICS AND CHEMISTRY COURSES AND THIS WAS DUE TO THE TIMELY STRUCTURING OF THE TRAINING AND EVALUATION PROCESSES CONSIDERING BLOOM'S TAXONOMY. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.